Variability of sinapic acid derivatives during germination and their contribution to antioxidant and anti-inflammatory effects of broccoli sprouts on human plasma and human peripheral blood mononuclear cells. Issue 8 (6th August 2020) - Olszewska, Monika Anna; Granica, Sebastian; Kolodziejczyk-Czepas, Joanna; Magiera, Anna; Czerwińska, Monika Ewa; Nowak, Pawel; Rutkowska, Magdalena; Wasiński, Piotr; Owczarek, Aleksandra
Abstract : Broccoli sprout extract rich in sinapic acid derivatives prevents oxidative changes in human plasma and modulates inflammatory response in PBMCs. Abstract : Broccoli sprouts represent a health-promoting food, rich in antioxidant and anti-inflammatory phytochemicals, among which sulfur compounds are most extensively investigated. In this study, the phenolics of broccoli sprouts ( Brassica oleracea var. italica 'Cezar') were examined for variability during germination and influence on the bioactivity of sprouts. In the sprouts germinated in darkness, 31 compounds were identified by UHPLC-PDA-ESI-MS 3 (18 sinapic acid derivatives, 8 glucosinolates, and 5 flavonoids) with sinapoyl components (SADs) prevailing among polyphenols. The total SADs decreased during germination (down to 4.85 mg per g dw in 6-day-sprouts), but the concurrent changes in molecular structures of the leading compounds (sinapine was replaced by sinapate sugar esters and sinapic acid) increased the antioxidant capacity of the sprouts. The glucosinolate-depleted 6-day-sprout extract (34.2 mg SADs per g dw) effectively protected human plasma components against peroxynitrite-induced oxidative damage in vitro (reduced the levels of 3-nitrotyrosine, lipid hydroperoxides and thiobarbituric acid-reactive substances) and enhanced the non-enzymatic antioxidant status of plasma. It also downregulated the release of pro-inflammatory cytokines (TNF-α, IL-6) from LPS-stimulated human peripheral blood mononuclear cells and increased the production of IL-10, an anti-inflammatory mediator. The relevant activity parameters of sinapic acid indicated that SADs might be linked to the observed effects. The results support the application of broccoli sprouts in oxidative stress- and inflammation-related diseases and the role of SADs as their bioactive components next to glucosinolates.